2021
DOI: 10.3390/ijms222111556
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Molecular Mechanisms of Alzheimer’s Disease Based on Network Analysis

Abstract: The complex pathology of Alzheimer’s disease (AD) emphasises the need for comprehensive modelling of the disease, which may lead to the development of efficient treatment strategies. To address this challenge, we analysed transcriptome data of post-mortem human brain samples of healthy elders and individuals with late-onset AD from the Religious Orders Study and Rush Memory and Aging Project (ROSMAP) and Mayo Clinic (MayoRNAseq) studies in the AMP-AD consortium. In this context, we conducted several bioinforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 84 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…GEM is an in silico representation of the metabolism where the interactions between metabolites and the biochemical reactions are formulated in a sparse stoichiometric matrix and the relationship between genes and reactions by Boolean rules (GPR rules). Moreover, GEM is used to simulate the role of the microbiome in the development of PD [ 70 , 71 ] or to study psychiatric diseases [ 72 ] and AD [ 73 ] in humans and PD-like phenotypes in mice [ 74 ]. However, brain metabolism has specific properties that must be considered before applying CBM.…”
Section: Introductionmentioning
confidence: 99%
“…GEM is an in silico representation of the metabolism where the interactions between metabolites and the biochemical reactions are formulated in a sparse stoichiometric matrix and the relationship between genes and reactions by Boolean rules (GPR rules). Moreover, GEM is used to simulate the role of the microbiome in the development of PD [ 70 , 71 ] or to study psychiatric diseases [ 72 ] and AD [ 73 ] in humans and PD-like phenotypes in mice [ 74 ]. However, brain metabolism has specific properties that must be considered before applying CBM.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, propanoate, inositol phosphate, glycerophospholipid and biotin metabolic pathways were identified to be perturbed in both variant and non-variant models of the same dataset. Propanoate metabolite is known to be neuroprotective and associated with brain-gut axis (Bayraktar, et al, 2021). A study showed that changes in the levels of inositol phosphate metabolic enzymes were correlated with amyloid beta peptide formation and tau hyperphosphorylation in AD (Stygelbout, et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown low levels of B 6 , B 12 , or folate lead to elevated levels of Aβ aggregates in neurons of transgenic mice models of Alzheimer’s disease 30 , 31 , 73 . B 6 is a cofactor that is involved in dopaminergic, and GABAergic synapse function 74 . The cholinergic synapses are also deregulated in Alzheimer’s disease 75 .…”
Section: Discussionmentioning
confidence: 99%